Exploring Pragmatic Competence in Formal Communicative Contexts: The case of thanking by native and non-native speakers of Greek - Athanasia Gkouma; Maria Andria; Georgios Mikros (Universitat Autònoma de Barcelona, 2020)
The aim of the current study is to investigate the role of second language (L2) proficiency in the pragmatic competence of learners of L2 Greek. More specifically, it aims at exploring whether L2 proficiency can have an impact on the strategies that L2 learners use in order to express the speech act of thanking in L2 Greek. Participants were thirty-one (N=31) learners of Greek at different proficiency levels (from A2 to C2) who were enrolled in a summer intensive course of Greek at a university language school in Athens, Greece. Additionally, a group of native speakers of Greek has been included as a baseline (N=30). Oral data were elicited through a series of open role plays which represented various communicative situations with different social parameters. Furthermore, a retrospective verbal protocol has been used in order to gain more insights into the way L2 learners perform the speech act of thanking. Results showed that there is a difference in the number of strategies of L2 learners across the different proficiency levels, which is more evident between beginners and advanced learners. However, findings seem to suggest that the role of proficiency is not clear-cut and it also depends, firstly, on the social parameters of each communicative situation and also on learners' familiarization with each situation. The study concludes by discussing some implications for L2 pedagogy.